Cutaneous Metastases from Primary Hepatobiliary Tumors as the First Sign of Tumor Recurrence following Liver Transplantation - Adam T. Hauch; Joseph F. Buell; Margit McGowan; Parisha Bhatia; Eleanor Lewin; Mary Killackey; Nathan J. Shores; Luis A. Balart; Martin Moehlen; Bob Saggi; Anil S. Paramesh (Case Reports in Transplantation)
Cutaneous metastasis from hepatobiliary tumors is a rare event, especially following liver transplantation. We report our experience with two cases of cutaneous metastases from both hepatocellular carcinoma and mixed hepatocellular/cholangiocarcinoma following liver transplantation, along with a review of the literature.